Emotion regulation and psychological well-being in teacher work engagement: A case of British and Iranian English language teachers. (April 2021) - Greenier, Vincent; Derakhshan, Ali; Fathi, Jalil
Abstract: Employing a sequential explanatory mixed-methods approach, this study investigated the role of emotion regulation and psychological well-being (PWB) as predictors of work engagement through using 108 British and 255 Iranian English language teachers as a sample. A multi-group structural equation modelling was performed to identify differences and similarities in the way emotion regulation and PWB could predict work engagement among British and Iranian English teachers. The valid measuring instruments of the three constructs were administered to collect the data in the two contexts. The results demonstrated measurement invariance, including both metric and scalar invariance, revealing that the constructs underlying the three scales possessed the same theoretical structure across two groups (i.e., British vs. Iranian). It was also revealed that both emotion regulation and PWB significantly predicted work engagement for the whole sample of British and Iranian teachers. However, PWB appeared to be a stronger predictor of work engagement. Moreover, some cross-cultural differences were identified in the regression coefficients. On the whole, the association of the PWB and work engagement was stronger for British teachers. The qualitative data analysis uncovered a number of categories and themes contributing to explaining differences between British and Iranian teachers. The results and implications are further discussed.